TRADE-OFFS: UNDERSTANDING FUTURE TRADE OPTIONS FOR SCOTLAND. (2022) - Figus, Gioele; McGregor, Peter; McIntyre, Stuart; Roy, Graeme
Abstract: Trade issues lie at the heart of the two biggest constitutional challenges the UK has faced in decades: Brexit and Scottish independence. Brexit has demonstrated the economic importance of borders and led to renewed calls for Scottish independence. While there are a range of possible trading arrangements an independent Scotland could pursue, all of them involve economically significant change. In this paper, we describe Scottish trade patterns and review the range of options that a newly independent Scotland might have for its trading arrangements. We then model the relative economic importance of these different potential trading arrangements.